(untitled) (CAHIERS MAGELLANES-NS, 2024)
This article examines effective methodologies for teaching economic terms in English, highlighting strategies that improve comprehension and retention. Key approaches include vocabulary-building techniques, contextual learning, and applied learning through real-life examples. Vocabulary grouping, vocabulary notebooks, and etymological analysis build a strong linguistic foundation. Contextual learning—using case studies, role-playing, and project-based assignments—engages students with terms in practical scenarios. Real-life applications, such as interpreting graphs, analyzing news articles, and using digital tools, further solidify understanding. Together, these methodologies provide a comprehensive framework for teaching economic vocabulary, fostering both linguistic proficiency and economic literacy.